Determinación de la dosis óptima del coagulante sulfato férrico a partir del pH en el tratamiento del agua de bombeo para la recuperación de harina de pescado de la empresa pesquera Cantabria S.A. - Coishco - Baca Capa, Sergio Javier (2016)
The fishing sector is a strategic activity for the food security of Peru and the world. The anchoveta resource is the source of fishmeal production, a fundamental food in the feeding of terrestrial and aquatic animals. For Peru from the economic point of view, the fishery is an important source of foreign exchange, with emphasis on marine fisheries, small-scale artisanal fisheries and aquaculture. The process of coagulation-flocculation in the treatment of pumping water, is done experimentally, at the laboratory level to perform the test of jars. This way of carrying out this process must be exact. Within this coagulation-flocculation process the one that has wide relevance is the coagulation, because if this is done erroneously, the flocculation could not be carried out successfully. The present thesis proposes a mathematical model in which the cubic interpolation of the experimental data of the coagulation process is applied to carry out it correctly, by means of the calculation of the optimum dose of ferric sulphate coagulant from the pH in the treatment of the water Of pumping in the Environmental Separator (HILLER) for the recovery of fish meal. The proposed model focuses on the application of ion balance solutions. Thus the values for the 16 samples of anchovy production show an optimal dose of ferric sulphate within the pH between 5 and 6, which are validated with the recommendations of the suppliers of Ferric Sulfate which indicates that the optimal dose of ferric sulphate coagulant is Found at a pH greater than 5